2000
DOI: 10.1016/s0735-1097(00)00629-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction occurring in versus out of the hospital: patient characteristics and clinical outcome

Abstract: In-hospital AMI occurred in 6.8% of patients. Time to intervention was shorter; however, the use of reperfusion therapy for in-hospital AMI was not different from that for prehospital AMI. In particular, primary angioplasty seems to be underused in these patients. This, as well as the selection of patients, may result in the high hospital mortality rate of 27.3%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 21 publications
5
52
0
1
Order By: Relevance
“…were done, which could exclude high-risk patients. This is supported by in-hospital mortality of 12–14% [23, 24]and 1-year mortality of 20–28% [23, 25, 26]reported in large unselected AMI populations.…”
Section: Discussionmentioning
confidence: 69%
“…were done, which could exclude high-risk patients. This is supported by in-hospital mortality of 12–14% [23, 24]and 1-year mortality of 20–28% [23, 25, 26]reported in large unselected AMI populations.…”
Section: Discussionmentioning
confidence: 69%
“…There were 34 patients in the noncardiac admission group including postsurgery, respiratory failure, and 4 of the miscellaneous patients had cancer (n=2) and gastrointestinal symptoms (n=2). In comparison with patients admitted for noncardiac reasons, patients admitted for cardiac reasons had lower mortality rates in-hospital, at 30 days (2.0% versus 17.7%; P=0.012 for both) and at 1 year (6.1% versus 32.4%; P=0.002), and shorter LOS (3 [2, 7.5] versus 6 [4,9]; P=0.008), as well. Patients initially admitted for cardiac reasons also tended to have shorter diagnostic ECG-to-balloon In-hospital death, n (%) Outcomes of in-hospital STEMI patients split by pre-and postprotocol implementation are shown in Table 4.…”
Section: Methodsmentioning
confidence: 95%
“…In 1986, L'Abbate et al 8 reported an overall mortality rate of 29% for 55 patients who sustained a Q-wave AMI while in-hospital. In 2000, Zhan et al 9 reported 403 inpatients with AMI (STEMI and non-STEMI) had a mortality rate nearly twice that of outpatients (27.3% versus 13.9%), and increased comorbidities, as well. In 2006, Maynard et al 10 reported on 792 AMI patients, including 75 with STEMI, who developed AMI while in-hospital within the Department of Veterans Affairs Health System.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline clinical conditions and associated treatments may lead to more atypical presentations, obscuring prompt identification of acute myocardial ischemia, which is often detected by changes in clinical status or incidental telemetry findings. [10][11][12] It is little surprise, then, that they appear to have worse short-term and long-term outcomes. Mortality in these patients may be driven by noncardiac causes, confounding the results of the development of STEMI protocols.…”
Section: Circulationmentioning
confidence: 99%
“…The literature on patients with onset of acute myocardial infarction while hospitalized is sparse; in general, these patients are a heterogeneous group with complex comorbid disease, prolonged time to treatment, and worse outcomes. 10,11 One study of 48 patients that focused exclusively on in-hospital STEMI reported that, perhaps as a result of their complex clinical conditions, the time between onset of ischemia (if identifiable) and ECG was widely variable and the time between ECG and angiography and PCI, when offered, was prolonged. Nearly 30% did not undergo reperfusion therapy because of concomitant disease and active contraindications.…”
mentioning
confidence: 99%